KERJASAMA NATIONAL CENTRAL BUREAU (NCB) INTERPOL INDONESIA DENGAN PEMERINTAH KAMBOJA DALAM MENANGANI KASUS PERDAGANGAN MANUSIA YANG MENIMPA WARGA NEGARA INDONESIA DI KAMBOJA TAHUN 2021 - 2022 - Tarisya Alifia, (2023)
Human trafficking remains a persistent threat that haunts people from various countries around the world. Indonesia, as an archipelagic nation with a large population, is not exempt from this threat. When the pandemic hit in 2020, human traffickers continued to intensify their various methods to trap their victims. The widespread use of social media further complicated the situation, ultimately erasing vulnerable points in the human trafficking victim's journey in Indonesia. This was also experienced by Indonesian citizens who became victims of human trafficking in Cambodia in mid-2021. Being a case with the highest reported incidents of human trafficking post-pandemic, the Indonesian government finally developed strategies to combat this issue. Involving stakeholders, the government invited the National Central Bureau (NCB) of Interpol Indonesia, a member of the world's largest police organization, to participate. The participation of NCB Interpol Indonesia is expected to assist Indonesia in establishing cooperation with the Cambodian government in handling Indonesian citizens who are victims of human trafficking in Cambodia. The goal of this study is to examine how an Intergovernmental Organization (IGO), in this case NCB Interpol Indonesia, collaborates with the government of a country as a representative of Indonesia, with the intention of utilizing the results of this cooperation on a broader scale. Keywords: Human Trafficking, Bilateral Cooperation, International Organizations.